PEMBUATAN SNACK BAR dariTEPUNG BIJI SAGA POHON (Adenanthera Pavonina L.) dengan PENAMBAHAN BUAH NANGKA KERING - Ganang Romadhon; Yusmarini Yusmarini; Shanti Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2021)
Snack bar is a snack like a beam that generally consists of rice, cereals and added with dry fruit which is equipped with other ingredients such as nuts and honey. Related to that, the snack bar in this research was made from a combination of saga tree seeds flour and dried jackfruit. The purpose of this research is to obtain a snack bar with the best sensory and chemical characteristics. This research used a completely randomized design (CRD) with five treatments and three repetitions. The data obtained were analyzed statistically using analysis of variance (ANOVA) and followed with Duncan's new multiple range test (DNMRT) at 5% level. The treatment in this research was the difference in the ratio between saga tree seeds flour and dried jackfruit, that is SN1 (40:60), SN2 (45:55), SN3 (50:50) and SN4 (55:45). The results showed that the difference in the ratio between saga tree seeds flour and dried jackfruit had a significant effect at all observation parameters, both chemical and sensory. SN4 treatment with ratio of saga tree seeds flour : dried jackfruit (55:45) is the best treatment that most favored by the panelists and descriptively brownish in color, scented of saga seeds and jackfruit, flavored of jackfruit, had a soft density, and had chemical characteristics that are 20.63%, % moisture content,2.44 % ash content, 8.68% fat content, 16.68% protein content, 50,88% carbohydrate content and 3.68% crude fiber content.Keywords: snack bar, saga tree seeds flour, dried jackfruit